Perbandingan Hukum Penyalahgunaan Posisi Dominan dalam Persaingan Usaha di Indonesia dan Korea Selatan: Comparative Law on Abuse of Dominant Position in Business Competition in Indonesia and South Korea - Fraya Layola Nainggolan; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2025)
Competition is very needed to improve the quality of human life, healthy competition is needed so that justice and welfare occur for every community which can have a positive and negative impact on business competition or the occurrence of unhealthy business competition. Unhealthy business competition is competition between business actors who carry out production activities of goods or services that are carried out dishonestly that hinders competition between business actors. The main problem is how the similarities and differences in the regulations regarding the abuse of the dominant position between the business competition law in Indonesia and South Korea and how the KPPU and KFTC establish a ban on the abuse of the dominant position. This article uses normative research methods, descriptive, drawing conclusions using deductive methods. The result of the discussion and conclusion of this article is that there are similarities and differences in regulations in Indonesia and South Korea in determining market share, the market concerned and limiting competition in the market, unfair sales actions and assessment based on approach. In addition, KPPU and KFTC determine the abuse of the dominant position by assessing the elements and can impose sanctions.